Ovariectomy Activates Chronic Low‐Grade Inflammation Mediated by Memory T Cells, Which Promotes Osteoporosis in Mice. (25th February 2020) - Cline‐Smith, Anna; Axelbaum, Ariel; Shashkova, Elena; Chakraborty, Mousumi; Sanford, Jessie; Panesar, Prabhjyot; Peterson, Macey; Cox, Linda; Baldan, Angel; Veis, Deborah; Aurora, Rajeev
ABSTRACT: The loss of estrogen (E2 ) initiates a rapid phase of bone loss leading to osteoporosis in one‐half of postmenopausal women, but the mechanism is not fully understood. Here, we show for the first time how loss of E2 activates low‐grade inflammation to promote the acute phase of bone catabolic activity in ovariectomized (OVX) mice. E2 regulates the abundance of dendritic cells (DCs) that express IL‐7 and IL‐15 by inducing the Fas ligand (FasL) and apoptosis of the DC. In the absence of E2, DCs become long‐lived, leading to increased IL‐7 and IL‐15. We find that IL‐7 and IL‐15 together, but not alone, induced antigen‐independent production of IL‐17A and TNFα in a subset of memory T cells (TMEM ). OVX of mice with T‐cell–specific ablation of IL15RA showed no IL‐17A and TNFα expression, and no increase in bone resorption or bone loss, confirming the role of IL‐15 in activating the TMEM and the need for inflammation. Our results provide a new mechanism by which E2 regulates the immune system, and how menopause leads to osteoporosis. The low‐grade inflammation is likely to cause or contribute to other comorbidities observed postmenopause. © 2020 American Society for Bone and Mineral Research.